Pentecostalism and the Universal Church of the Kingdom of God in Thohoyandou, South Africa - Matshidze, Pfarelo Eva (Stellenbosch : Stellenbosch University, 2012)
Thesis (MPhil)--Stellenbosch University, 2005.